2021
DOI: 10.18203/2394-6040.ijcmph20210816
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study to assess the socio-demographic and morbidity profile among under-five children in a resettlement colony of Bihar

Abstract: Background: The development of our society and the world largely depends on the health of the children in their first five years. These first five years lay down the foundation of their future mental and physical health. India has the largest number of children in the world. India also contributes to more than 20% of the child deaths in the world. children who are born in rural areas, poor household or illiterate families, are at major risk of dying before turning six years of age. Aim was to assess the health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…7 Kumar et al in their study among under-5 children in Bihar observed, 71.00% boys and 58.00% girls were morbid. 8 The difference was statistically significant. Pandey et al observed poor immunization coverage i.e.,65.00% in Bhojpur district of Bihar.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…7 Kumar et al in their study among under-5 children in Bihar observed, 71.00% boys and 58.00% girls were morbid. 8 The difference was statistically significant. Pandey et al observed poor immunization coverage i.e.,65.00% in Bhojpur district of Bihar.…”
Section: Discussionmentioning
confidence: 86%
“…Special focus needs to be put in neglected rural residential areas to promote health of the under-5 children. 8 Avoidable illness and disabilities among under-5 children are prevented by routine immunization against some specific diseases. Immunization coverage is associated with various socio-demographic factors.…”
mentioning
confidence: 99%